Hydrogen-deuterium exchange mass spectrometry of Mtr4 with diverse RNAs reveals substrate-dependent dynamics and interfaces in the arch. Issue 7 (5th April 2022) - Zhang, Naifu; Olsen, Keith J; Ball, Darby; Johnson, Sean J; D'Arcy, Sheena
Abstract: Mtr4 is a eukaryotic RNA helicase required for RNA decay by the nuclear exosome. Previous studies have shown how RNA en route to the exosome threads through the highly conserved helicase core of Mtr4. Mtr4 also contains an arch domain, although details of potential interactions between the arch and RNA have been elusive. To understand the interaction of Saccharomyces cerevisiae Mtr4 with various RNAs, we have characterized RNA binding in solution using hydrogen-deuterium exchange mass spectrometry, and affinity and unwinding assays. We have identified RNA interactions within the helicase core that are consistent with existing structures and do not vary between tRNA, single-stranded RNA and double-stranded RNA constructs. We have also identified novel RNA interactions with a region of the arch known as the fist or KOW. These interactions are important for RNA unwinding and vary in strength depending on RNA structure and length. They account for Mtr4 discrimination between different RNAs. These interactions further drive Mtr4 to adopt a closed conformation characterized by reduced dynamics of the arch arm and intra-domain contacts between the fist and helicase core.